Exploring Social Justice Through Art in a Community Health Nursing Course - Dosani, Aliyah; Lehman, Jocelyn; Cuncannon, Alexander (Teaching and Learning Inquiry, 2024)
Social justice and health equity are foundational to community health nursing. Arts-based pedagogy has learning and reflexive value for community and population health education within nursing and health professions curricula have been increasingly used in health care and in promoting health, including in nursing education. However, research has not explored the use of arts to teach community health nursing students about social justice. The objective of this study was to understand how the inclusion of a collaborative artistic process relates to the understanding of social justice issues for second-year baccalaureate nursing students enrolled in a community health nursing course. Visual art and symbolic components were added to an existing group concept mapping assignment of community health nursing interventions from a social justice approach. We engaged in analysis within interpretive phenomenological inquiry to understand and share students’ experiences with constructing and giving meaning to symbols and art pieces, internalizing the concept of social justice, and collaborating with group members. Students used symbols and visual representation to explore social justice and health. Students’ narrative reflections encompassed experiences finding personal power, engaging in empathy, reflecting on their own position and privilege, and benefitting from non-traditional forms of learning. Students recounted group processes that deepened their understanding of concepts, increased their appreciation of the need for advocacy, and enabled creative freedom in the context of collective vision. The addition of a collaborative creative, artistic process enhanced students’ learning about social justice and health. Read the corresponding ISSOTL blog post here.